Survival time of post and cores: A 16 year retrospective follow-up study. (February 2022) - Vogler, Jonas Adrian Helmut; Lehmann, Moritz; Rehmann, Peter; Wöstmann, Bernd
Abstract: Objectives: The retrospective survival study (1995–2004) by Balkenhol et al. [1] . led to changes in the decision-making process for treatment with post and cores (special focus on the covering prosthetic restoration while deciding for treatment with post and cores, high primary friction at the try-in stage for conventional cementation, only indirect fabrication technique, no semi-precious alloy) in our clinic. The aim of this study was to examine the influence of these changes on the survival probability. Materials and Methods: In the observation period (2004–2020) 653 patients received in total 953 post and cores. The patient files were analysed due to the parameters: Type of covering prosthetic restoration, location, type of tooth, luting material, post and core material, bone attachment, therapist and cause of failure. According to the previous study the survival probability was assessed using Kaplan-Meyer analysis. Cox regression was used to assess the risk of failure and identify possible covariates. Results: The average survival time of the post and cores was 10.9 years. The cumulative failure rate was 28.2%. A significant influence on the survival time (Kaplan-Meyer analysis) could be found for the parameters: Type of covering prosthetic restoration, location, type of tooth, post and core material and bone attachment. The multifactorial survival analysis (Cox regression) showed a significant influence of the age of the patient at the time of fitting the post, the type of covering prosthetic restoration and the bone attachment. Conclusions: The changes in the decision-making process did not lead to a better survival probability. Clinical significance: The conclusions stated in the previous study were not strict enough. Treatments with post and cores should be critically scrutinized on the basis of covering prosthetic restoration and bone attachment. Post and cores under primary crown retained RPDs should be avoided because of the bad survival probability.